A trilha dos ninhos de aranha : o romance de Italo Calvino no contexto da resistência italiana - Moraes, Cintia da Silva (2017)
The path to the spiders’ nest, published in 1947, two years after the World War II (1939- 1945) is the first novel by Italo Calvino, the fruit of an exercise of remembrance of his experiences as a partisan in the Ligure Mountains. To better understand that, we will start from the historical context of its production: war, civil war, resistance and their reflexes on the various segments of society at that time. Anchored in the reflections of Antonio Gramsci, we will consider questions about the formation of Italy as a nation, the role of the intellectuals, and the question of language as national unity, also present in Calvin's novel.